Basin perspectives on the Water–Energy–Food Security Nexus - Lawford, R.; Bogardi, J.J.; Marx, S.; Jain, S.; Wostl, C. P.; Knüppe, K.; Ringler, Claudia; Lansigan, F.; Meza, F. (Elsevier, 2013)
This article summarizes some major factors that influence the Water–Energy–Food (W–E–F) Security Nexus and how they are perceived in different basins. These findings are based on a survey that was undertaken for the Global Catchment Initiative (GCI) within the Global Water System Project (GWSP) complemented by case studies for a transboundary basin (the Lake Winnipeg Basin), a national basin (Yellow Basin in China), and a number of the basins in a nation (India). The analysis also includes ranking of river basin issues related to the WEF Nexus based on the views of experts in nine basins. Based on this analysis, factors that have affected the evolution of the W–E–F Nexus, including the applications of Earth observations, are discussed. The study concludes that the W–E–F Nexus could be an effective vehicle for advancing water and sustainability issues and recommends research and demonstration projects to test the extent to which the WEF framework could be helpful in increasing understanding and collaborative governance approaches.